(untitled) (Global Journal of Science Frontier Research, 2022)
Juvenile idiopathic arthritis JIA is a heterogeneous pathology with uncertain causative factors and prognosis stemming from an immune system dysfunction with the development of autoimmune reactions The most distinctive and potentially most severe of these is systemic JIA sJIA a disease characterized by sharp rises in temperature and rash A thorough understanding of the complex of immune regulatory mechanisms along with genetic analysis reveals complex relationships between autoimmune reactions and auto inflammation Sequencing of 15 auto inflammatory genes was performed in 62 patients with JIA 26 oligoarthritis 20 polyarthritis 16 systemic Studies have shown that 16 25 8 patients with the clinical JIA phenotype had changes in nucleotide sequence in the genes encoding auto inflammatory immune response proteins NOD2 changes were in 12 19 3 of them and 1 change in each of the 4 patients NLRP12 heterozygote c 1343G C p Gly448Ala MEFV pathogenic heterozygous c 2082G A p Met694Ile ADA2 heterozygote c 145C T Arg49Trp PSTPIP1 heterozygote c 806T A p Ile269A in the group of studied children with JIA The study will allow identifying individual genetic loci of JIA risk expand understanding of the pathogenesis and spectrum of phenotypic manifestations of the disease improve diagnosis and prediction of its course as well as reveal new opportunities for monitoring patients with JIA and their personalized therapy